T ToXic01 Mar 2010 27 0 May 9, 2010 #1 [Solved]Find all of the real and imaginary zeros for the polynomial function Find all of the real and imaginary zeros for the polynomial function f(x)=x^3-7x^2+x-7 Answer is 7,-i,i How do I solve this to get to the answer Last edited: May 9, 2010

[Solved]Find all of the real and imaginary zeros for the polynomial function Find all of the real and imaginary zeros for the polynomial function f(x)=x^3-7x^2+x-7 Answer is 7,-i,i How do I solve this to get to the answer

Jhevon MHF Hall of Honor Feb 2007 11,663 4,210 New York, USA May 9, 2010 #2 ToXic01 said: Find all of the real and imaginary zeros for the polynomial function f(x)=x^3-7x^2+x-7 Answer is 7,-i,i How do I solve this to get to the answer Click to expand... Factor by grouping \(\displaystyle x^3 - 7x^2 + x - 7 = x^2(x - 7) + (x - 7)\) \(\displaystyle = (x - 7)(x^2 + 1)\) Now do you see how to get to the answer?

ToXic01 said: Find all of the real and imaginary zeros for the polynomial function f(x)=x^3-7x^2+x-7 Answer is 7,-i,i How do I solve this to get to the answer Click to expand... Factor by grouping \(\displaystyle x^3 - 7x^2 + x - 7 = x^2(x - 7) + (x - 7)\) \(\displaystyle = (x - 7)(x^2 + 1)\) Now do you see how to get to the answer?

P Plato MHF Helper Aug 2006 22,456 8,631 May 9, 2010 #3 \(\displaystyle x^3-7x^2+x-7=x^2(x-7)+(x-7)=(x-7)(x^2+1)\)

T ToXic01 Mar 2010 27 0 May 9, 2010 #4 Jhevon said: Factor by grouping \(\displaystyle x^3 - 7x^2 + x - 7 = x^2(x - 7) + (x - 7)\) \(\displaystyle = (x - 7)(x^2 + 1)\) Now do you see how to get to the answer? Click to expand... so if i set this equal to zero i get the answer

Jhevon said: Factor by grouping \(\displaystyle x^3 - 7x^2 + x - 7 = x^2(x - 7) + (x - 7)\) \(\displaystyle = (x - 7)(x^2 + 1)\) Now do you see how to get to the answer? Click to expand... so if i set this equal to zero i get the answer

pickslides MHF Helper Sep 2008 5,237 1,625 Melbourne May 9, 2010 #5 ToXic01 said: so if i set this equal to zero i get the answer Click to expand... Yep make \(\displaystyle x^2 + 1=0\) and \(\displaystyle x - 7=0\)

ToXic01 said: so if i set this equal to zero i get the answer Click to expand... Yep make \(\displaystyle x^2 + 1=0\) and \(\displaystyle x - 7=0\)